Efektivitas Senam Tai Chi terhadap Nilai Angkle Brachial Indeks Pada Diabetes Mellitus Tipe 2 Perokok dan non Perokok Di Kota Bima - Haris Haris; Martiningsih Martiningsih; Ahamd Ahamd; Sri Handayani Sri Handayani; Ns. Zulkarnain (Jurnal Health Sains, 2023)
Diabetes mellitus is a metabolic disorder that is often associated with modern lifestyle habits such as smoking. The content of toxins in cigarettes can cause blood circulation disorders in the legs which can be measured through examination of the value of the ankle brachial pressure index. This comparative descriptive study aims to identify differences in anklebrachial pressure index values in smokers and non-smokers of diabetes mellitus patients. The sampling technique is in the form of purposive sampling involving 100 respondents to type 2 diabetes mellitus. The results of data analysis with the paired t test obtained a p-value value of 0.0001 > 0.05 there was an effect of giving tai chi movement on the value of ABI in smoker respondents, and obtained a p value of 0.01 > 0.05 there was an influence of giving tai chi movements on the value of ABI in non-smoker respondents. The conclusions of this study show that there are differences in the value of the ankle brachial pressure index in smokers and non-smokers of diabetes mellitus patients after being given tai chi. To prevent the occurrence of complications of diabetes mellitus, it is hoped that you will maintain a good lifestyle such as not smoking, maintaining a diet, and exercising regularly.